Retinal waves are likely to instruct the formation of eye-specific retinogeniculate projections - Feller, Marla B (BioMed Central, 2009)
Prior to eye-opening and the development of visual responses, the retina exhibits highly correlated spontaneous firing pattens termed retinal waves. Disruption of the normal spontaneous firing pattern either genetically or pharmacologically prevents the eye-specific refinement of retinogeniculate afferents. Here I provide the evidence that retinal waves play an instructive role in this process. In addition, I argue that a full understanding requires an identification of the features of retinal activity that drive the refinement as well as an understanding of mechanisms that transform these signals into axonal rearrangements.